When tropical and subtropical congeners met: Multiple ancient hybridization events within Eriobotrya in the Yunnan‐Guizhou Plateau, a tropical‐subtropical transition area in China - Chen, Sufang; Milne, Richard; Zhou, Renchao; Meng, Kaikai; Yin, Qianyi; Guo, Wei; Ma, Yongpeng; Mao, Kangshan; Xu, Kewang; Kim, Young‐Dong; Do, Truong Van; Liao, Wenbo; et al. (Molecular Ecology, 2022)
Global climate changes during the Miocene may have created ample opportunities for hybridization between members of tropical and subtropical biomes at the boundary between these zones. Yet, very few studies have explored this possibility. The Yunnan‐Guizhou Plateau (YGP) in Southwest China is a biodiversity hotspot for vascular plants, located in a transitional area between the floristic regions of tropical Southeast Asia and subtropical East Asia. The genus Eriobotrya (Rosaceae) comprises both tropical and subtropical taxa, with 12 species recorded in the YGP, making it a suitable basis for testing the hypothesis of between‐biome hybridization. Therefore, we surveyed the evolutionary history of Eriobotrya by examining three chloroplast regions and five nuclear genes for 817 individuals (47 populations) of 23 Eriobotrya species (including 19 populations of 12 species in the YGP), plus genome re‐sequencing of 33 representative samples. We concluded that: (1) phylogenetic positions for 16 species exhibited strong cytonuclear conflicts, most probably due to ancient hybridization; (2) the YGP is a hotspot for hybridization, with 11 species showing clear evidence of chloroplast capture; and (3) Eriobotrya probably originated in tropical Asia during the Eocene. From the Miocene onwards, the intensification of the Eastern Asia monsoon and global cooling may have shifted the tropical‐subtropical boundary and caused secondary contact between species, thus providing ample opportunity for hybridization and diversification of Eriobotrya, especially in the YGP. Our study highlights the significant role that paleoclimate changes probably played in driving hybridization and generating rich species diversity in climate transition zones.